2019
DOI: 10.1101/846550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear mechanics of lamin filaments and the meshwork topology build an emergent nuclear lamina

Abstract: The nuclear laminaa meshwork of intermediate filaments termed laminsfunctions as a mechanotransduction interface between the extracellular matrix and the nucleus via the cytoskeleton. Although lamins are primarily responsible for the mechanical stability of the nucleus in multicellular organisms, in situ characterization of lamin filaments under tension has remained elusive. Here, we apply an integrative approach combining atomic force microscopy, cryoelectron tomography, network analysis, and molecular dynami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…In this study, the nuclear membrane of T2DM-ADSCs was shown to be deformed and swollen. In the cellular nucleus, the intermediate filament protein, lamin, forms a network structure called lamina, 23 which connects the nuclear membrane with chromatin. The laminae stabilize the nuclear structure and are involved in chromatin organization, gene transcription, and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the nuclear membrane of T2DM-ADSCs was shown to be deformed and swollen. In the cellular nucleus, the intermediate filament protein, lamin, forms a network structure called lamina, 23 which connects the nuclear membrane with chromatin. The laminae stabilize the nuclear structure and are involved in chromatin organization, gene transcription, and DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to microtubules or actin filaments, which have persistence lengths of ~7 -22 µm and several mm, respectively, keratin filaments are much more flexible (60). Their long α-helical building blocks allow them to accommodate high bending, similar to nuclear lamins (40,61). Previous studies showed that the persistence length of K8/K18 filaments can vary significantly between 300 -650 nm depending on the method used (46,62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Lamins are proposed to regulate nuclear mechanics not only through their non-linear mechanical properties as intermediate filament polymers but also through their influence on the organizational state of chromatin (e.g., euchromatin vs. heterochromatin) (26)(27)(28)(29). However, the individual contribution of each lamin isoform to nuclear stiffness is incompletely understood.…”
Section: Loss Of A-or B-type Lamins Compromises Nuclear Stiffness and Alters Heterochromatin Levelsmentioning
confidence: 99%